Do Public University Business Incubators in Indonesia Have Good Performance? - Hasanah Sarjono, Atina; Setiawan Slamet, Alim; Anggraeni, Elisa (Jurnal Manajemen dan Organisasi, 2024)
Indonesia's innovation management focuses on enhancing competitiveness, independence, and economy through research and development, with university-based business incubators connecting research and commercialization. Three public incubators have an A rating, indicating an 86 percent survival rate. This research aims to explore the level of efficiency of business incubator performance, and level of tenant satisfaction, and classify business incubator services into different levels of satisfaction/dissatisfaction through a satisfaction matrix. The research employs a quantitative method, utilizing a Paired Sample t-test and IPA (Importance Performance Analysis) matrix. The results show that job creation (on average per year) exceeds the benchmarking value, so it can be said that the public universities’ business incubator has contributed to job creation. There are differences in all variables for the level of effectiveness and importance which have negative values or tenants feel dissatisfied with the services provided by the business incubator, business incubator services that need attention are IP protection and startup legal, exhibitions and business matching with investors or potential partners, business network support after graduation and business expansion assistance after graduation.